2019
DOI: 10.1088/1755-1315/368/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Saturated and unsaturated hydraulic conductivity of synthetic gel structures in coarse textured soil substrates

Abstract: Saturated and unsaturated hydraulic conductivity as a function of a thermodynamic potential (pressure) of soil water K(P) are investigated in the sandy samples with admixtures of strongly swelling polymer hydrogels (SSPHs) in a wide concentration range from 0.01 to 0.3 %SSPHs. The author’s original centrifugation method has been used along with a kinetic model of the water removal process, which enables to determine the function of water conductivity of gel compositions operating in an unsteady state. In satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The effect of hydrogels on saturated hydraulic conductivity ( Ks ) has been inconsistent though most studies on soil hydraulic conductivity have focused on Ks (as opposed to unsaturated hydraulic conductivity). Out of the 14 studies surveyed that investigated the effects of hydrogels on Ks , nine of the 14 studies indicated a decrease in Ks [ 10 , 32 , 45 , 57 , 64 , 65 , 74 , 83 , 87 ], however, three studies [ 28 , 66 , 88 ] reported an increase and three studies reported an initial decrease in Ks then a subsequent increase in Ks with time [ 60 , 88 , 89 ]. In two of the studies [ 60 , 89 ], the subsequent increase in Ks seem to increase over the original Ks .…”
Section: Impacts Of the Application Of Hydrogels On Soil Hydraulic Pr...mentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of hydrogels on saturated hydraulic conductivity ( Ks ) has been inconsistent though most studies on soil hydraulic conductivity have focused on Ks (as opposed to unsaturated hydraulic conductivity). Out of the 14 studies surveyed that investigated the effects of hydrogels on Ks , nine of the 14 studies indicated a decrease in Ks [ 10 , 32 , 45 , 57 , 64 , 65 , 74 , 83 , 87 ], however, three studies [ 28 , 66 , 88 ] reported an increase and three studies reported an initial decrease in Ks then a subsequent increase in Ks with time [ 60 , 88 , 89 ]. In two of the studies [ 60 , 89 ], the subsequent increase in Ks seem to increase over the original Ks .…”
Section: Impacts Of the Application Of Hydrogels On Soil Hydraulic Pr...mentioning
confidence: 99%
“…Much of the evidence for decreases in Ks was found in studies that used synthetic hydrogels. A total of six studies [ 32 , 45 , 57 , 74 , 83 , 87 ] using various synthetic hydrogels definitively argue that hydrogels decrease Ks . Four of the six studies applied hydrogels to sandy soils underscoring the need for more studies using other soil textures.…”
Section: Impacts Of the Application Of Hydrogels On Soil Hydraulic Pr...mentioning
confidence: 99%
See 3 more Smart Citations